2017
DOI: 10.1123/pes.2016-0213
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing Parent Perceptions of Physical Activity in Families of Toddlers With Neurodevelopmental Disorders: The Parent Perceptions of Physical Activity Scale (PPPAS)

Abstract: Purpose The purpose of this study was to examine a new tool (PPPAS = Parent Perceptions of Physical Activity Scale-Preschool) developed to study parental perceptions of physical activity (PA) among parents of toddler and preschool age children. Method 143 children (mean age 31.65 months; 75% male) and their parents were recruited from a neurodevelopmental clinic. Parents completed questionnaires, and both a psychologist and a physician evaluated the children. 83% of the children received a diagnosis of Autis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
0
8
0
3
Order By: Relevance
“…The year of publication ranged from 1999 to 2018 (median = 2014). Out of the 35 studies that were considered for primary meta‐analyses, 31 studies and 30 studies respectively were considered for the meta‐analysis that examined the prevalence of BMI ≥ 85th and 95th percentile for age and sex in children with ASD. Ten studies were included in the meta‐analyses that examined the relative risk of BMI ≥ 85th percentile among children with ASD, while 11 studies were included in the meta‐analysis that examined the pooled relative risk of BMI ≥ 95th percentile among children with ASD.…”
Section: Resultsmentioning
confidence: 99%
“…The year of publication ranged from 1999 to 2018 (median = 2014). Out of the 35 studies that were considered for primary meta‐analyses, 31 studies and 30 studies respectively were considered for the meta‐analysis that examined the prevalence of BMI ≥ 85th and 95th percentile for age and sex in children with ASD. Ten studies were included in the meta‐analyses that examined the relative risk of BMI ≥ 85th percentile among children with ASD, while 11 studies were included in the meta‐analysis that examined the pooled relative risk of BMI ≥ 95th percentile among children with ASD.…”
Section: Resultsmentioning
confidence: 99%
“…The Parent Perceptions of Physical Activity Scale (PPPAS) is a 25-item parent-report questionnaire (Lakes et al, 2017 ) available in two forms—one for infants (Lakes et al, 2019b ) and the second for young children (Lakes et al, 2017 ), which was used in this study. The PPPAS requires about 10 min to complete and assesses parental perceptions of the benefits of (18 items) and barriers to (7 items) PA, using a 4-point Likert scale with responses ranging from Strongly Disagree (1) to Strongly Agree (4).…”
Section: Methodsmentioning
confidence: 99%
“…The PPPAS requires about 10 min to complete and assesses parental perceptions of the benefits of (18 items) and barriers to (7 items) PA, using a 4-point Likert scale with responses ranging from Strongly Disagree (1) to Strongly Agree (4). Sample items for the Benefits subscale included: “Increasing activity increases my child's level of physical fitness,” “Physical activity in childhood will make my child healthier,” “Exercising helps my child sleep better at night,” and “Physical activity improves overall functioning for my child.” Sample items for the Barriers subscale included: “I worry that my child will not be accepted by others if he/she participates in a group sport or activity program” and “Physical activity will make my child frustrated.” Principal components analysis (PCA) for the 25 items yielded two components (Lakes et al, 2017 ): (1) beliefs in the benefits of physical activity and (2) perceptions of barriers to physical activity. The PPPAS was initially developed for and studied in children under the age of five who were experiencing developmental difficulties as a tool to assess parental perceptions that might impact their PA support behaviors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that contemporary children spend more than 7 hours a day in front of a screen [33], an activity tracking device was selected as a primary factor for this study as it could be appealing to the youth interested in technology and could serve as a facilitator to participation in physical activity among families. Previous literature regarding families and physical activity was either focused on the parents’ perceptions of the benefits of and barriers to physical activity among their children [34] or revealed that the children were not very active with their parents [35]. However, a recent systematic review suggested that family-based interventions can be an effective way to improve physical activity participation among families [36].…”
Section: Introductionmentioning
confidence: 99%